A narrative of arrival and return in Imbolo Mbue's Behold the Dreamers - Gasztold, Brygida (Orbis litterarum, 2025)
Imbolo Mbue's novel Behold the Dreamers offers a conscious contextualizing of the movement back to the homeland by those who arrive uninvited and face the hostility of reluctant hosts. For centuries, North America has attracted many with a prospective dream of happiness, better conditions of living, higher purchasing power, and a share of all the good things of modern life, from industrial products to education. The glamour of greener pastures abroad has held a steady grip on the generations of potential immigrants. While the U.S. cherishes the idea of itself as a land so abundant in promise and possibility that no newcomer would ever want to leave, the reality turns out to be more complex for Mbue's protagonists—the Cameroonian immigrants Jende and Neni Jonda, who enjoy few privileges but endure varying degrees of hardships and discrimination. Their story falls into the category of what Adam Kirsch (2016) no longer calls “immigrant” but “migrant” literature:— “[m]igrant novels focus on characters for whom America is a stage of life rather than a final destination. Their protagonists may come to the First World legally or illegally, from a position of strength or weakness. But they see life in America, and often Europe, as means to an end—education, wealth, political freedom—rather than ends in themselves” (Kirsch, The global novel: Writing the world in the 21st century. Columbia Global Reports 2016, 82). My paper examines the reasons for their arrival in the American Promised Land, discussing push and pull factors, and follows their decision to go back to Cameroon, signaling those aspects of the North American experience that challenge and impede their success. Return as the critical paradigm shifts the perspective, bringing Africa from the periphery of the developing world to the narrative center. I adopt a post‐colonial feminist approach, to demonstrate how gender impacts the experience of immigration and their decision‐making process, gesturing towards return migration as a viable alternative to a traumatic existence for those with no legal rights to remain in the U.S.